A Survey on The Recent Developments and Modern Hardware Systems for Enhancing the Intelligent Transportation System - Devaraju hanumanthu, (AG Volumes, 2022)
High-performance Modern Hardware Devices (MHDs) are becoming more necessary due to the growing complexity of the Intelligent Transportation Systems (ITS), which includes a broad range of applications as well as services. Machine Learning (ML) approaches have made the performance problem more apparent in large-scale contexts. A successful use of machine learning (ML) in the area of intelligent transportation systems (ITS) has provided efficient as well as optimal solutions to issues that were previously solved using conventional analytical and statistical methodologies. It's a difficult challenge to solve in the age of ML to meet the hardware deployment demands of ITS because of the time, space, environment, and cost aspects involved. MHDs were used in this study to examine the most current literature on ML-driven ITS, which focused on performance measures. Survey results may be used as a starting point for building appropriate hardware, enabling the integration of machine learning (ML) into ITS, as well as bridging the gap between academic research and real-world deployments.